Penerapan Profile Matching untuk Efektifitas Kompetensi Kandidat Dosen Pembimbing di Perguruan Tinggi - Erick Sorongan; Danar Retno Sari; Eva Dinar (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Accuracy in the selection or determination of human resources in an organization greatly affects the achievement of the company's final goals. Currently, it is not uncommon to determine a candidate for a leader or a position not based on the abilities or skills of the selected candidate, but because of the closeness or compatibility between policy makers. Although there have been many studies that have proven that the quality of Human Resources affects the achievement of the organization's vision, few have discussed this relationship by involving the initial selection or determination process using the advantages of systems and information technology. The purpose of this research is to create an electronic-based system that can be used by a company to determine prospective candidates who meet the criteria or requirements desired by the company or organization. The method used to make a decision on the selection of candidates adjusts to the algorithm contained in the Porfile Matching method by determining the percentage value criteria aspect. This method assumes that the ideal level of predictor variables must be met by candidate subjects by giving weight to each variable. The experimental results of a decision support system using a profile matching algorithm that is coded into the program to determine or select a supervisor who is in accordance with the title of a student's final project at a university shows the compatibility between the Education, Research and Support aspects required by the university. The results of this study can provide implications for HR management practitioners in determining the suitability between HR and position maps. For academics, this can increase understanding of the effect of a profile matching algorithm-based decision support system on the effectiveness and objectivity of determining candidates in an organization.